GUIDO OREFICE'S EFFORT FOR BEING A GOOD FATHER IN ROBERTO BENIGNI'S LIFE IS BEAUTIFUL MOVIE (1999): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - MITAMARTIANASARI, DWI (2011)
This research investigated how is effort of Guido Orefice influences his personality in Roberto Benigni‟s Life is Beautiful movie, especially viewed from individual psychological approach. The objectives of the research are to analyze the movie based on the structural elements of the movie and to analyze the personality structure of major character based on the individual psychological approach. The research paper belongs to the qualitative research. The object of the study is the effort of Guido Orefice in Life is Beautiful. The data source comes from primary data source that is the Life is Beautiful move and the secondary data sources are other sources related to the movie. The method of data analysis used in this study is descriptive analysis. From the result of analysis, it can be drawn some conclusions. Firstly, the structural elements of the movie present a good unity because it has related one to another. Roberto Benigni extends the theme of this movie is about the struggling of father during discrimination of race. Secondly, based on individual psychological analysis this movie reflects Guido sacrifices to safe his family during discrimination of race.